Predictors of cancer survivors’ response to a community-based exercise program - Brunet, Jennifer; Howell, Doris; Au, Darren; Jones, Jennifer M.; Bradley, Holly; Berlingeri, Antonia; Santa Mina, Daniel (Université d'Ottawa | University of Ottawa, 2019)
Objective: To explore the degree to which sociodemographic (i.e., age, sex, ethnicity, weight status, vocational status, marital status), medical (i.e., stage of cancer, treatment status, comorbidity burden), functional (i.e., selfrated health, exercise capacity), cognitive (i.e., exercise self-efficacy beliefs), and behavioural (i.e., program adherence, extra-curricular exercise) factors predicted cancer-related fatigue and quality of life among 224 cancer survivors who participated in the community-based Wellspring Cancer Exercise Program (WCEP). Design: Prospective, quasi-experimental single-group repeated measures design. Method: Data on predictors and outcomes were collected using self-report and objective measures upon enrollment in the program (week 0), every 10 weeks until program completion (weeks 10, 20, 30), and at 16-weeks follow-up (46 weeks). Data were analyzed using multilevel modeling. Results: In general, participants who were working or transitioning to work, rated their health better, and had higher exercise self-efficacy beliefs had lower cancer-related fatigue, and those who rated their health better and had higher exercise self-efficacy beliefs had higher quality of life. Also, there was a significant interaction between time and exercise self-efficacy beliefs for cancer-related fatigue and quality of life such that greater improvements were observed among participants with higher exercise self-efficacy beliefs. Conclusion: Cancer survivors’ perceptions of their health and their ability to exercise should be fostered to ensure they respond positively to exercise programs in terms of cancer-related fatigue and quality of life.
Keywords: Physical activity; Fatigue; Quality of life; Experimental study; Oncology